Más allá del color: proyecto etnoeducativo en la Institución Educativa Lorgia de Arco (2016)
Beyond the color: Ethnoeducative project at the IE Lorgia de Arco of Santander de la Cruz district - Moñitos Municipality, It is a work of systematization about the Afro-Colombian ethnoeducative process according to Decree 804 of 1995, that is to say, the collective construction of a global project of life, as an alternative proposal endogenous community development involving the community in general. Based on the sociocritic methodological paradigm, this study of qualitative kind, it is possible to reconstruct an ethnic, social and pedagogical process, based on the legal and educational empowerment of a community, which achieved through workshops and field practices, build themselves little by little, its institutional practices, its ethnoeducative practices and appropriate of an environmental didactic model, as a pedagogical and didactic strategies, a whole itinerary of significant educational activities on the problemist axes of identity, environmental culture, quality of life and community development, as a social evolution beyond color, from the perspective of human rights in educational contexts of affirmative action.